Protocol to purify and detect ubiquitinated phospholipids in budding yeast and human cell lines - Jun-ichi Sakamaki; Noboru Mizushima (STAR Protocols, 2023)
Summary: Ubiquitin is covalently conjugated to phospholipids as well as proteins; however, ubiquitinated phospholipids are less abundant than free ubiquitin and ubiquitinated proteins. Here, we describe protocols to purify ubiquitinated phospholipids in budding yeast and human cells based on their hydrophobicity. Ubiquitinated phospholipids are purified by Triton X-114 phase partitioning and affinity purification and verified by phospholipase D treatment. These protocols enable the detection of tagged as well as endogenous mono- and poly-ubiquitinated phospholipids by immunoblotting.For complete details on the use and execution of this protocol, please refer to Sakamaki et al..1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.